Scheduling single-machine problem based on just-in-time principles: a case study - Dantas, Joana D. (2014)
In this paper are applied heuristics that try to find good solutions for a static single machine scheduling problem. In the considered problem different processing times and due dates are used and no preemption is allowed. The heuristics applied consider several performance measures, which intend to be customer and enterprise oriented. Customer oriented performance measures are mainly related to the accomplishment of due dates while enterprise-oriented ones typically consider other time-oriented measures, like the makespan. The heuristics used in this work are focused on Just-in-Time principles and on different costumer and enterprise performance measures, although preference is given to customer-oriented measures, namely the total number of tardy jobs and the maximum tardiness.